Clonal haematopoiesis of indeterminate potential and cardiovascular events in systemic lupus erythematosus (HEMATOPLUS study). (17th February 2022) - David, Clémence; Duployez, Nicolas; Eloy, Philippine; Belhadi, Drifa; Chezel, Julie; Guern, Véronique Le; Laouénan, Cédric; Fenwarth, Laurène; Rouzaud, Diane; Mathian, Alexis; de Almeida Chaves, Sébastien; Duhaut, Pierre; et al.
Abstract: Objective: The detection of somatic mutations among the genes of myeloid cells in asymptomatic patients—defining clonal haematopoiesis of indeterminate potential (CHIP)—is associated with a predisposition to cardiovascular events (CVEs) in the general population. We aimed to determine whether CHIP was associated with CVEs in SLE patients. Methods: The study is an ancillary study of the randomized, double-blind, placebo-controlled, multicentre PLUS trial conducted from June 2007 through August 2010 at 37 centres in France, involving 573 SLE patients. The search for somatic mutations by high-throughput sequencing of 53 genes involved in clonal haematopoiesis was performed on genomic DNA collected at PLUS inclusion. CHIP prevalence was assessed in SLE and in a retrospective cohort of 479 patients free of haematological malignancy. The primary outcome was an incident CVE in SLE. Results: Screening for CHIP was performed in 438 SLE patients [38 (29–47) years, 91.8% female]. Overall, 63 somatic mutations were identified in 47 patients, defining a CHIP prevalence of 10.7% in SLE. Most SLE patients (78.7%) carried a single mutation. Most variants (62.5%) were located in the DNMT3A gene. CHIP frequency was related to age and to age at SLE diagnosis, and was associated with a lower frequency of aPLs. CHIP occurred >20 years earlier ( P  < 0.00001) in SLE than in controls. The detection of CHIP at inclusion was not found to be associated with occurrence of CVEs during follow-up [HR = 0.42 (0.06–3.21), P  = 0.406]. Conclusion: The prevalence of CHIP is relatively high in SLE for a given age, but was not found to be associated with incident CVEs. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT05146414.